Vibration Analysis of Composite Multilayer Floor of High-Speed Train - Ying Han; Wenjing Sun; Jinsong Zhou; Dao Gong (Shock and Vibration)
Mechanical properties of floor prototypes made for high-speed trains from composite multilayer floor structures of different materials and thicknesses were tested. Based on the test results, the equivalent mechanical parameters of different layers of the panels, core materials, etc., were calculated, and the multilayer mixed finite element model of the floor was built and verified. The multilayer mixed floor model was introduced into the car body of a high-speed train, and the test signals of the high-speed train were used as inputs to calculate the vibration response of composite floor structure. Vibration spectra of the high-speed train composite floor made of different materials and structures were compared and analyzed. The results show that the calculation of the floor vibration response of the vehicle car body within the framework of the equivalent model of the multilayer structure based on the mechanical performance test is an effective method to evaluate vibration characteristics. The vibration isolation performance of the stainless steel panel floor is better than that of the aluminum alloy panel, but its large mass is not favorable in lightweight body design. The vibration energy of birch core material floor is significantly smaller than the alder core material of the same size. The vibration isolation performance of the floor enhanced with the increase in the thickness of the outer metal panel, but when the outer metal panel thickness exceeds 0.8 mm, the influence becomes small. Therefore, the stainless steel-birch core composite floor with a large panel thickness has the best vibration isolation performance and can be used for the floor above the bogie and the suspended excitation source. Then, an optimal analysis considering mass and vibration characteristics was carried out, and the results show that there exists an optimal solution for the high-speed train. Regarding the overall design basis of the vehicle, the aluminum alloy panel lightweight structure can be used in combination with other general parts.